Effect of Sucrose Addition on Viscosity, pH, Total Yeast, and Hedonic Quality of Water Kefir Roselle - Hastrawirid, Rangga Wasi; Dwiloka, Bambang; Rizqiati, Heni (Diponegoro University, 2024)
Red Roselle (Hibiscus sabdariffa L.) is a plant known for its high antioxidant content, making it a suitable ingredient for probiotic water kefir beverages. This study aimed to investigate the impact of different sucrose concentrations in roselle water kefir on viscosity, pH, total yeast count, and hedonic quality. The experimental design used was a Completely Randomized Design. The treatments varied based on sucrose concentrations 6%, 9%, 12%, and 15% (w/v). The findings revealed that the addition of 12% sucrose resulted in a viscosity of 1.22 cP, pH of 2.93, total yeast count of 2.15 CFU/ml, and the highest hedonic quality. In conclusion, the addition of 12% sucrose (w/v) proved to be the optimal treatment, yielding a beverage with suitable viscosity, acceptable pH, favorable total yeast count, and an overall hedonic quality embraced by the panelists.